2009
DOI: 10.1111/j.1439-0531.2009.01381.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Progesterone Withdrawal on Pregnancy‐Related Parameters During Post‐Implantation Early Pregnancy Loss

Abstract: Pharmacologically-induced luteolysis or treatment with an antiprogestin in early post-implantation pregnancy in dogs results in asynchronous death and resorption of conceptuses, indicating variable rates of response of individual conceptuses towards progesterone deficiency. This variability also seems to occur in bitches showing pregnancy failure in response to spontaneous luteal deficiency. In a total of 10 beagle pregnancies (two consecutive pregnancies of five bitches), abortifacient treatments beginning on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…A growing amount of studies have demonstrated that the impedance to uterine artery blood flow was significantly increased in RPL patients compared with controls . Impaired uterine artery blood perfusion is considered as a pathogenesis of RPL, which would affect the endometrial receptivity and play an important role in regulating successful pregnancy . However, Isaksson et al showed that there was no significant correlation between uterine artery blood perfusion and the occurrence of spontaneous fetal loss .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A growing amount of studies have demonstrated that the impedance to uterine artery blood flow was significantly increased in RPL patients compared with controls . Impaired uterine artery blood perfusion is considered as a pathogenesis of RPL, which would affect the endometrial receptivity and play an important role in regulating successful pregnancy . However, Isaksson et al showed that there was no significant correlation between uterine artery blood perfusion and the occurrence of spontaneous fetal loss .…”
Section: Discussionmentioning
confidence: 99%
“…6,7,9,10 Impaired uterine artery blood perfusion is considered as a pathogenesis of RPL, which would affect the endometrial receptivity and play an important role in regulating successful pregnancy. 11,14 However, Isaksson et al showed that there was no significant correlation between uterine artery blood perfusion and the occurrence of spontaneous fetal loss. 15 We found that, during the midluteal phase, the mPI, mRI and mS/D values for uterine arteries were significantly higher in RPL patients compared with the controls, which was consistent with our previous preliminary findings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations